Previous Audit Opinions, Leverage, and Company Size on Going Concern Audit Opinions - Noviansyah Rizal (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
An economic entity is projected to be used continually for an undetermined duration that extends beyond an accounting period . This study aims to determine whether the previous audit opinion, leverage, and company size affect the going concern audit opinion. The population of this research are manufacturing companies in the basic & chemical industry sector which are listed on the IDX in 2016-2018. The sample was determined using purposive sampling, the final sample was 35 companies. Testing this hypothesis using logistic regression analysis using the SPSS 21 program. The results of this study state that previous audit opinions, leverage and company size have no effect on going concern audit opinions.